Aplicação de diferentes metodologias do Value at Risk (VaR) para mensuração do risco de mercado de uma carteira teórica de ações - Fernandes Júnior, Marcelo Aparecido [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Value at Risk is a risk measure widely used by financial institutions to assist in the allocation of the minimum capital requirement. This study presents the regulation of risk management for financial institutions and the following VaR estimation methods: Historical Simulation – HS, Exponentially Weighted Moving Average – EWMA, Autoregressive Conditional Heterocedasticity – GARCH (GARCH Normal and Skew-tGARCH) and Extreme Value Theory – EVT. For the analysis, a theoretical portfolio was built containing the shares of Itaú, Bradesco, Petrobras and Vale, from which the time series of a period referring to the COVID-19 pandemic (january 2020 to september 2021) was observed, which served to predict the maximum potential losses with 99% confidence for the month of august and semptember 2021, according to each of the methods. The models were approved by Backtesting according to Kupiec's criterion, with the exception of two univariate EWMA models that were disapproved and the Theory of Extreme Values, which was not implemented due to its restrictions. The models showed satisfactory results even in a period of high volatility.

O Value at Risk é uma medida de risco amplamente utilizada por instituições financeiras para auxiliar na alocação do requerimento mínimo de capital. Neste trabalho foi abordada a regulamentação da gestão de riscos para instituições financeiras e os seguintes métodos de estimação do VaR: Simulação Histórica (HS), Média Móvel Exponencialmente Ponderada (EWMA), Autorregressivo de Heteroscedasticidade Condicional Generalizado (GARCH Normal e Skew-t-GARCH) e Teoria dos Valores Extremos (EVT). Para análise foi construída uma carteira teórica contendo as ações do Itaú, Bradesco, Petrobrás e Vale, das quais foram observadas as séries temporais de um período referente a pandemia da COVID-19 (janeiro de 2020 até setembro de 2021), que foram utilizadas para prever as perdas máximas potenciais com 99% de confiança para os meses de agosto e setembro de 2021, segundo cada um dos métodos. Os modelos foram aprovados pelo Backtesting segundo critério de Kupiec, com exceção de dois modelos EWMA univariados que foram reprovados e da Teoria dos valores extremos que não foi implementada devido suas restrições. Os modelos apresentaram resultados satisfatórios mesmo em um período de alta volatilidade.
Application of different Value at Risk (VaR) methodologies to measure the market risk of a theoretical stock portfolio
Keywords: Value at risk; Market risk; Stock portfolio; Historical simulation; Exponentially weighted moving average; GARCH; Extreme value theory; Valor em risco; Risco de mercado; Carteira de ações; Simulação histórica; Suavização exponencial; Volatilidade condicional; Teoria dos valores extremos